The Effectiveness of Wearing Mask and Physical Distancing in Preventing the COVID-19 Transmission - Tri Nyantosani Widyawardani; Eti Poncorini Pamungkasari; Bhisma Murti (Journal of Epidemiology and Public Health, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The increase in the number of cases was rapid, and spread to various countries in a short time. Based on epidemiological and virological studies, it has been proven that COVID-19 is transmitted from symptomatic (symptomatic) people to other people who are in close proximity through droplets and aerosols. The application of health protocols is very effective in preventing transmission. Wearing masks, keeping a distance and washing hands are very important in preventing the spread of COVID-19.Subjects and Method: This study is a meta-analysis using the PICO model. The population is the general public (adults over 18 years), the intervention is to wear masks properly and keep a distance. The comparison is not wearing a mask properly and not keeping a distance. The outcome is prevention of the spread of COVID-19. The articles used in this study were obtained from three databases, namely Google Scholar, PubMed, and Science Direct. The keywords to search for articles were “mask” AND “covid transmission” “physical distancing” AND “cross sectional study”, from 2019 to 2021. The selection of articles was carried out using the PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 case studies from the African, American and Asian continents were selected for systematic review and meta-analysis. The results showed that the use of masks was 2.10 times effective in preventing transmission of COVID-19 and was statistically significant (aOR= 2.10; 95% CI= 1.54 to 2.85; p<0.001). Maintaining an effective distance of 2.35 times in preventing transmission of COVID-19 and statistically significant (Aor= 2.35; 95% CI= 1.44 to 3.83; p<0.001).Conclusion: Wearing a mask and keeping a distance is effective in preventing the spread of COVID-19. Keywords: mask, physical distancing, covid transmission Correspondence:Tri Nyantosani Widyawardani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: nyantosani@gmail.com. Mobile: +62811284836.